Population pharmacokinetic analysis of orally-administered ruxolitinib (INCB018424 Phosphate) in patients with primary myelofibrosis (PMF), post-polycythemia vera myelofibrosis (PPV-MF) or post-essential thrombocythemia myelofibrosis (PET MF) - Chen, Xuejun; Williams, William V; Sandor, Victor; Yeleswaram, Swamy (Journal of clinical pharmacology, 2013)
Ruxolitinib is a selective inhibitor of Janus kinase 1 and 2, which is approved to treat intermediate or high-risk myelofibrosis. The population pharmacokinetics for ruxolitinib were characterized by a modeling dataset of 272 subjects from a Phase 2 and a Phase 3 study and validated by an external validation dataset of 142 subjects from a second Phase 3 study. The PK of ruxolitinib was adequately described by a two-compartment disposition model with first-order absorption and linear elimination. All model parameters were estimated with good precision. Gender and body weight were identified as covariates for oral clearance (CL/F) and volume of distribution for central compartment (Vc/F), respectively. Apparent oral clearance was 22.1 and 17.7 L/h for a typical male and female subject, respectively, with 39.1% unexplained inter-individual variability (IIV). The typical Vc /F for a subject with a median weight of 72.9 kg was estimated to be 58.6 L, with 28% unexplained IIV. The model predictive performance was validated by visual predictive check (VPC) and the external validation dataset. This analysis suggests that effects of gender and body weight on ruxolitinib PK are not clinically significant and hence no dose adjustment is needed based on gender and weight.